Rekonstruksi Hukum Mediasi Penal Sebagai Alternatif Penyelesaian Perkara Tindak Pidana Lingkungan Hidup Berbasis Keberlanjutan Lingkungan: Reconstruction of Penal mediation law as an alternative to environmental criminal action-based Environment sustainability solutions - Laksminarti, Laksminarti (Pencerah Publik, 2019)
This research aims to obtain an overview of the construction of the Law on the mediation of penal as an alternative to environmental criminal action-based sustainability. In environmental matters, about the criminal environment, the legislation does not provide an ADR (Alternative Dispute Resolution) opportunity in which the parties are permitted to choose a dispute resolution Through negotiations, mediation, and conciliation. This is contained in article 85 paragraph (2) of UUPPLH stating that the settlement of disputes outside the courts does not apply to environmental criminal acts as provided for in this law. This condition of enforcement gives birth to a variety of thoughts that give alternative crime settlement of criminal act outside the Court of mediation of penal. Using a descriptive analysis obtained the idea that to conduct mediation of the penal as an alternative criminal settlement, it is necessary to reform criminal legal structure. The results of the research show that criminal law reconstruction is necessary considering that the institution of Penal mediation organizers has not been contained in the current structure of criminal law. Constructing Penal mediation as an alternative to settlement of Environmental criminal act into the criminal law system in Indonesia is expected to provide improvement and progress in environmental law enforcement. That the settlement of environmental criminal acts through Penal mediation as part of the criminal law system, requires the arrangement in legal science legislation that tends to be critical and has characteristic Personality as "sociological jurisprudence".